Media and religion: the global view - Hoover, Stewart M.; Echchaibi, Nabil (Religion and society, 2021)
Frontmatter -- Acknowledgements -- Contents -- Introduction -- Conjuring the Religious, the Global and the Mediated -- High Tech Mediations, Low Tech Lifestyles: The Paradox of Natural Parenting in the Digital Age -- Multi-site Mediated Worship: Why Simulcast Sermons Need Live Local Praise Bands -- Silencing the Tongues of Angels? The Aesthetics of Destruction in Environmental Edens -- Anatta in Buddhism and Games: Emptiness and the Magic Circle -- The National Museum and Religious Identity: The “Islamic Period” at Iran’s National Museum -- Media, Religion, and the Fabric of Culture and Communication in Contemporary Brazil -- Digitizing Jesus: Expanding Publics and Cultivating Civility with the Jesus Film Smartphone App -- Digital Media and Imperial Formations: The 2012 Lady Gaga Controversy in South Korea -- Media Curation and Re-emergent Religion in Ghana’s Roadside Public Sphere -- Religion, Media and Culture in India: Hindutva and Hinduism -- Contributors -- Index